2022
DOI: 10.1002/emp2.12603
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and medical management of body‐packers in French Guiana between 2010 and 2015

Abstract: Background French Guiana is used as a drug trafficking pipeline of cocaine to Europe. The number of arrests for transporting cocaine in corpore has increased exponentially in recent years. Since 2010, Cayenne Hospital's emergency care unit has applied a medical management protocol system for body‐packers. Our objective was to describe the epidemiology of body‐packers and to evaluate medical management. Method A retrospective descriptive study was performed among patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Improvements in packaging quality and complications from surgery are responsible for the increasing tendency to treat these cases conservatively. 5,6,21 Two large retrospective studies confirmed the safety of conservative management for the treatment of body packers. These studies analyzed 1181 and 1250 subjects, who required surgery in only 2% and 1.6% of cases, respectively.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Improvements in packaging quality and complications from surgery are responsible for the increasing tendency to treat these cases conservatively. 5,6,21 Two large retrospective studies confirmed the safety of conservative management for the treatment of body packers. These studies analyzed 1181 and 1250 subjects, who required surgery in only 2% and 1.6% of cases, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Currently, a conservative approach to these patients is recommended. Improvements in packaging quality and complications from surgery are responsible for the increasing tendency to treat these cases conservatively 5,6,21 . Two large retrospective studies confirmed the safety of conservative management for the treatment of body packers.…”
Section: Discussionmentioning
confidence: 98%
“…Mechanical complications related to the ingestion of foreign body ingestion such as bowel obstruction and or perforation are less frequently described but can have lethal consequences [6,8]. Overall, these complications are scarce, and French studies observed a rate of severe complications from 1.4 to 3.5% [3,4].…”
mentioning
confidence: 99%
“…A symptomatic patient should be admitted to an ICU. The surgical removal of drug packets in patients with cocaine toxicity or bowel obstruction remains the standard of care but endoscopy can also be considered as an alternative to surgery in some cases [4]. Benzodiazepines are recommended in case of neuropsychiatric symptoms or seizures.…”
mentioning
confidence: 99%
See 1 more Smart Citation